LAN CONFIGURATION TECHNIQUES - Diana Desy Desy (Majalah SIKOMTEK, 2003)
Studying the concept of LAN is the first step of the learning process going out for someoneconducts a computer network. A good understanding of the functions of a computer networkwill be much help a person to operate a computer network system. Studying the concept ofthis LAN can be assumed as a learning function of network system managers who have theability to regulate the work of all computer terminals connected to one another in a computernetwork.